Mirella Carbone’s Paso doble: An Autobiographical Spell for the Body, Fold of Silence, a Tribute - Bonomini, Sandra (2020)
This article is an analysis, tribute and dialogue with the performance Paso doble by Mirella Carbone. Carbone starts from the autobiography to create presences—becomings—of itself, with which criticizes identity impositions that the classist, colonial, macho, racist, and homophobic Lima demands. A «little man» in white suit and a doll drawn with a chalk by the artist activate the memory, open personal archives and bring important issues to the present. From the non-hegemonic figures that the artist presents, as well as silence and repression, I propose Paso doble as a place of the visible and possible. From the perspective of feminist and decolonial theories, latent issues in Paso doble are approached in order to understand the effects of coloniality—of power, knowledge and being—in the body, subjectivity and steps from the artist.